Improving microbial protein synthesis in the rumen of sheep fed fresh tofu waste by crude tannin extract of Acacia mangium - Wina, Elizabeth; Yulistiani, D; IWR, Susana; Tangendjaja, B (Indonesian Journal of Animal and Veterinary Sciences, 2012)
Tannin can be found in many tropical plants and the presence of tannin may reduce the nutritional value of feed. However, it can give beneficial effect as it protects the protein from its excessive degradation in the rumen. Tofu waste is abundant in a country, including Indonesia, where tofu is produced widely. A feeding trial on sheep to study the effect of tannin on microbial protein synthesis and condition of rumen fermentation, digestibility and N retention of feed containing tofu waste was conducted. Fifteen sheep were allocated to one of 3 treatments, i.e: 1) control treatment, feed without tannin, 2) feed + tannin treatment and 3) feed + tannin + polyethylene glycol (PEG) treatment. The sheep was placed in the individual metabolism cage. They were fed with treatment feed for 14 days and then, the following 7 days, faeces and urine were collected. At the end of the treatment, rumen fluid was taken from each sheep before and after feeding. Rumen parameter (pH, ammonia, SCFA, protozoa) and microbial protein synthesis, digestibility, nitrogen retention were observed. Results showed that inclusion of 4% tannin in the feed depressed ammonia production in the rumen of sheep before and 3 hours after morning feeding. Total SCFA and individual SCFA were not different among treatments. Tannin did not affect daily feed intake. Tannin lowered the dry matter, organic matter and protein digestibilities but it significantly reduced ADF digestibility (P < 0.05) and tended to reduce NDF digestibility (P < 0.1). However, tannin increased the microbial protein synthesis. PEG addition was expected to bind tannin and alleviate the negative effect of tannin. Key Words: Tannin, Acacia Mangium, Polyethylene Glycol, Tofu waste, Digestibility